Using three-dimensional printing in the teaching and learning of Human Anatomy: An integrative literature review (Research, Society and Development, 2023)
The study of Human Anatomy has undergone numerous changes over time. Traditional teaching methods, such as the study of cadavers, have been limited and the production of anatomical models using three-dimensional (3D) printing has provided an innovative solution for use in teaching practices. The objective of the present study was to analyze the possibility of applying three-dimensional printing to the teaching and learning of Human Anatomy in medical schools. A descriptive analysis was carried out, based on an integrative literature review of studies published between 2013 and 2022, using the terms (DeCS/MeSH): "Three-Dimensional Printing", "Medical Education" and "Anatomy", applied in English and their correspondents in Spanish and Portuguese. 3D printing is an important tool for studying Human Anatomy, enabling better identification of anatomical points in the different systems, providing greater long-term retention of the information studied and enhancing anatomical learning, in conjunction with other printed and virtual materials, cadaveric parts and augmented virtual reality. The importance of investing in the use of 3D printing in educational approaches and exploring possible improvements in medical education is highlighted.